Poetry into painting: Mallarmé, Picasso, and punning - Shingler, Katherine (Sage, 2013)
This article gives a critical assessment of the relationship between the poetry of Stéphane Mallarmé and the Cubist painting and collage of Pablo Picasso. Taking in a range of critical sources that have insisted on Picasso’s ‘mallarmisme’, the article sets out to shift scholarly debate away from its focus on Picasso’s punning reference to Un coup de dés in a 1912 collage, and its suggestion of a dialogue between poet and painter around high art and its relationship to popular, commercial forms of production. It proposes that we instead focus our attention on the punning structures shared by Mallarmé and Picasso’s work more generally – structures which give rise to a sense of simultaneity, or overlaps of meaning, and which ultimately suggest that in engaging with Mallarmé’s poetry Picasso was self-consciously reflecting on the notion of painting as a kind of language, with its own syntax.